Analisis Upaya Guru Dalam Mengatasi Kesulitan Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Pancasila Kelas II Di SDN 1 Keraton - Halimah, Siti Nur; Labudasari, Erna; Dianasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is the process of acquiring knowledge, understanding, and behavior that is in accordance with the needs known as education. High-quality human resources are the main goal of education. This study aims to analyze the learning difficulties of students in the subject of Pancasila Education class II at SD Negeri 1 Keraton, these learning difficulties are characterized by the inability of students not to master the subject matter within the specified time, not achieving learning outcomes that are in accordance with their abilities, showing a low level of achievement compared to other students and showing bad personalities such as being impolite, naughty, and not adapting to the scope of the lesson, identifying factors causing learning difficulties originating from internal factors of students which include disorders or psycho-physical deficiencies, such as cognitive, affective, psychomotor and external factors of students include every situation and environmental conditions that do not support student learning activities including family, community, and school. In dealing with this, teachers make various efforts, both as educators who adjust learning methods, as mentors who provide individual attention and motivation, and as assessors to evaluate the process and learning outcomes of students fairly and comprehensively. Pancasila education is very important for every citizen and serves as a guideline for living life as a good citizen and in accordance with the values of Pancasila. Learning difficulties are when students do not achieve the expected learning outcomes. This study also uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and questionnaires. The object of the study was conducted at SDN 1 Keraton, Class II. The results of the study indicate that the teacher's efforts in overcoming students' learning difficulties in the Pancasila education subject can be seen from the results of the questionnaire about the factors that influence learning difficulties obtained 15 students who experienced learning difficulties is 68.18% and 7 students who did not experience learning difficulties is 31.82%.